Posisi Stratigrafi dan Petrogenesis Intrusi Pendul, Perbukitan Jiwo, Bayat, Kabupaten Klaten, Jawa Tengah - Surono Surono; Udi Hartono; Sam Permanadewi (Pusat Survei Geologi, 2006)
The Pendul Intrusion consists of andesite, diabas, diorite, and gabbro; that are widely distributed within the Jiwo Hills, south of Klaten, Central Jawa. K/Ar datings of 4 rock indicate that there are two magmatism episodes; Middle Eocene - Early Oligocene (39,82 - 30,04 Ma) and Middle Miocene (17,22 - 13,85 Ma). Trace element concentrations of the Pendul rocks characterize that the magma was originated from subduction environment as a result of mantle wedge melting. The rocks are characterized by low Nb relative to K and La contents. The rare earth element signatures indicate that the Pendul magmas might have come from defferent parent magmas. The Middle Eocene - Early Oligocene parent magmas posses lower rare earth element concentrations than those of the Middle Miocene ones.Â Keywords: Bayat, Pendul Intrusion, two magmatism episodes, stratigraphy